2017
DOI: 10.1016/j.rmed.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two types of equal-intensity inspiratory muscle training in stable patients with chronic obstructive pulmonary disease: A randomised controlled trial

Abstract: In summary, in clinically stable patients with COPD, 8 weeks of R-IMT was superior to 8 weeks of equal-intensity T-IMT in improving HRQoL, degree of dyspnoea, and exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 27 publications
(24 reference statements)
0
33
0
12
Order By: Relevance
“…Dyspnea during constant and incremental load tests was significantly decreased with IMT alone compared with the control group reaching the clinical relevance only for the constant load test (two points reduction with the modified Borg scale) . The decrease of dyspnea between the two groups (CET group vs. CET +IMT group) was not different …”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Dyspnea during constant and incremental load tests was significantly decreased with IMT alone compared with the control group reaching the clinical relevance only for the constant load test (two points reduction with the modified Borg scale) . The decrease of dyspnea between the two groups (CET group vs. CET +IMT group) was not different …”
Section: Resultsmentioning
confidence: 76%
“…Two thousand and fifty‐seven articles were identified but only 43 studies (38 RCT, 2 CT, and 3 cohort studies) were included in the systematic review and 37 out of them in the meta‐analysis. Reasons for study exclusion are outlined in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Physical rehabilitation in CoPd remains an issue. The current literature provides a description of pulmonary rehabilitation, which should be recommended to all patients apart from the pharmacological treatment [14][15][16][17]. Unfortunately, among the published research results on the treatment of the disease, there are 9.8-15.95% of rehabilitation studies and 3.8-11.5% of those related to physiotherapy [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…in our opinion, to improve the quality of life of CoPd patients, it is necessary to employ daily kinesiotherapy, whose main means is breathing exercises, in combination with nebulizer therapy. Many studies have shown the positive effect of respiratory gymnastics [10,14,17,19] and physical training [1,3,9] on the indicators of external respiration function, namely the increase in forced expiratory volume in 1 second. The results of several randomized controlled studies have revealed that the use of manual therapy with physical training helps to improve physical performance [5,20].…”
Section: Discussionmentioning
confidence: 99%
“…Однако недавно проведенный метаанализ показал, что применение только ТДМ у больных с ХОБЛ средней и тяжелой стадии приводило к значительному снижению выраженности одышки. Кроме того, у этих пациентов наблюдалось улучшение переносимости физической нагрузки [14,35]. Таким образом, ТДМ может рассматриваться как дополнение к лечению у пациентов с ХОБЛ, которые не могут полноценно участвовать в общих физических тренировках вследствие наличия сопутствующей патологии, например, опорнодвигательного аппарата.…”
Section: показания для тдмunclassified